AMPLITUDE INDICATORS ELECTROCARDIOGRAM IN ATHLETES AND GIRLS WHO ARE NOT INVOLVED IN SPORTS, ADOLESCENCE - Kyrychenko, Y.V. (World of Medicine and Biology, 2013)
In this paper the peculiarities of amplitude electrocardiographic parameters in athletes of high level sports training and the girls who are not involved in sports.
Keywords: electrocardiography; amplitude; girls volleyball; athlete; nonsportsmen; adolescence